Traduction assistée par ordinateur – espérances trompeuses ou réalité possible ? Description lexicographique du vocabulaire des sucreries en québécois selon l’approche orientée objets - Chrupała, Aleksandra (Neophilologica, 2007)
The article presents the object-oriented method on the basis of a lexicographic description of the object category of “sweets”. The analysis covered several nouns confirmed by Office de la Langue Française au Québec. These are the forms to be found both in the French standard language and its Quebec variety. The nouns were described from the perspective of the object classes, and possible differences between the Quebec and European usage were signalled. The author notices that these differences concern morphology or syntax to a small extent whereas are limited to the level of lexis, which is visible in translations into Polish among other things. The lexicographic description according to the object-oriented method was illustrated with the results deriving from three exemplary nouns (caramel, bonbon, chocolat). As a conclusion, it was stated that all nouns examined can be placed in the object class of “sweets” defined by a set of predicates typical of a given class, and that a division of this class into sub-classes requires a more detailed analysis conducted using a richer linguistic material.